ANALYSIS OF THE EFFECT OF PRODUCT QUALITY, DISTRIBUTION CHANNELS, AND PERSONAL SELLING ON FISH SALES VOLUME AT PT LAUTAN PERSADA BELAWAN - Corri Satria Sihotang; Enda S. Padang; Jarungjung Hutagaol (Jurnal Ekonomi, 2022)
This study aims to determine how the influence of product quality, distribution channels, and personal selling on fish sales volume at PT Lautan Persada Belawan. This study uses the SPSS version 26 application. In this study the population used was all employees of PT Lautan Persada Belawan as many as 63 employees. The method used in this research is a quantitative approach. The results of this study product quality variables have a significant effect on sales volume with a significance of 0.000 and tcount 5.635. The distribution channel variable has a significant effect on sales volume with a significance of 0.000 and tcount of 4.120. The personal selling variable has a significant effect on sales volume with a significance of 0.005 and tcount of 2.889. Variables of product quality, distribution channels and personal selling simultaneously affect the volume of sales.